An innovative way to fabricate γ-TiAl blades and their failure mechanisms under thermal shock. (October 2021) - Gao, R.; Peng, H.; Guo, H.; Chen, B.
Abstract: The near-net-shape γ-TiAl blades were built by selective electron beam melting. As-fabricated material exhibits a good combination of microstructure homogeneity, tensile properties and thermal shock resistance at 700 °C owing to the optimised process parameters. The consistent and reliable approach to achieve this manufacturing success is elaborated. By performing thermal shock experiments at 900 °C, a new cracking mechanism has been identified. Through the post-mortem examinations, we reveal that such failure mode is most likely associated with the layer-by-layer strategy. Oxidation in conjunction with the surface topology is the underlying mechanism. Graphical abstract: Image, graphical abstract